PROGRAMMED CELL DEATH THE ROLE OF MITOCHONDRIA IN THE OCCASION OF APOPTOSIS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article is devoted to programmed cell death - apoptosis. The death of a cell after it has performed all its vital functions is apoptotic. This is a natural process. In doing so, the molecules that make up the cell are gradually broken down, allowing other cells in the same organism to use them. Apoptosis cannot be equated with necrosis. In apoptosis, the cells that kill the cells are genes. Apoptosis is a programmed death of a cell that is controlled by suicidal genes. The process of apoptosis is not rapid and it is different from necrosis. First the mitochondria, then the nucleus, and finally the cytoplasm breaks down into fragments, that is, the cell divides and forms apoptotic bodies, which are phagocytosed or dissolved by macrophages. Apoptosis, as an immunomodulatory form of cell death, plays a stabilizing role in maintaining the number of cells in the body. Although much is known and proven about apoptosis, the role of mitochondria in their origin is insufficient. Therefore, this article provides information on the effect of mitochondrial dysfunction on the development of programmed cell death - apoptosis.